The distribution of macro and micronutrients in the maize within separated digestate fertilizing: field trial - Kodymová, Jana; Švehláková, Hana; Kyncl, Miroslav; Bártková, Magdaléna (GeoScience Engineering, 2016)
Along with the current increase in the number of biogas plants, huge amounts of digestate, i.e. waste product, are being generated. The common practice in the Czech Republic is to plough the digestate into the land. In our field trial we compared the fertilizing effects of standard fertilizers applied in Czech with digestate as the only fertilizer (e.g. digestate fibre and digestate liquor) in real agricultural conditions, to find out whether a comparable amount of nitrogen is used in accordance with European legislation. Observed was the impact of separated digestate fibre and separated liquor on the soil fertility and quality on the basis of the distribution of macro- and micronutrients in plants, i.e. maize. The evaluation of growth increments in maize suggests that the fertilizing effects of digestate liquor or digestate fibre do not match the standard fertilizer in agriculture, but especially digestate liquor is comparable with other mineral fertilizers. Our field trial also shows that digestate liquor is a better fertilizer that digestate fibre, which may be explained by more appropriate ratios of available nutrients in digestate liquor. Digestate fibre may be recommended mainly for the aeration of clayey soil, but is not sustainable as fertilizer.